A simplified and unified model of multi-GNSS precise point positioning. Issue 1 (1st January 2015) - Chen, Junping; Zhang, Yize; Wang, Jungang; Yang, Sainan; Dong, Danan; Wang, Jiexian; Qu, Weijing; Wu, Bin
Abstract: Additional observations from other GNSS s can augment GPS precise point positioning (PPP) for improved positioning accuracy, reliability and availability. Traditional multi-GNSS PPP model requires the estimation of inter-system bias (ISB) parameter. Based on the scaled sensitivity matrix (SSM) method, a quantitative approach for assessing parameter assimilation, we theoretically prove that the ISB parameter is not correlated with coordinate parameters and it can be assimilated into clock and ambiguity parameters. Thus, removing ISB from multi-GNSS PPP model does not affect coordinate estimation. Based on this analysis, we develop a simplified and unified model for multi-GNSS PPP, where ISB parameter does not need to be estimated and observations from different GNSS systems are treated in a unified way. To verify the new model, we implement the algorithm to the self-developed software to process 1 year GPS/GLONASS data of 53 IGS (International GNSS Service) worldwide stations and 1 month GPS/BDS data of 15 IGS MGEX (Multi-GNSS Experiment) stations. Two types of GPS/GLONASS and GPS/BDS combined PPP solution are performed, one is based on traditional model and the other implements the new model. RMSs of coordinate differences between the two type of solutions are few μm for daily static PPP and less than 0.02 mm for GPS/GLONASS kinematic PPP in the North, East and Up components, respectively. Considering the millimeter-level precision of current GNSS PPP solutions, these statistics demonstrate equivalent performance of the two solution types.